2000
DOI: 10.2190/rvue-9xw7-tyrq-ejr8
|View full text |Cite
|
Sign up to set email alerts
|

Physical Training as a Substance Abuse Prevention Intervention for Youth

Abstract: Program evaluation data from school and community applications of a physical fitness drug prevention program is presented. A train-the-trainer methodology was applied to install the program in twenty-two settings within the state of Illinois. The physical training program consisted of exercise and educational modules delivered over a twelve-week time period that focused on learning values and life skills through exercise. Complete pre-post data were obtained on 329 participating youth at six school and communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 9 publications
0
49
0
1
Order By: Relevance
“…For instance, a 12-week training program targeting adolescents and focusing on learning values and life skills through exercise reported a significant decrease in several risk factors associated with substance abuse and a concomitant reduction in the percentage of individuals who use cigarettes, smokeless tobacco, and alcohol (Collingwood et al, 2000). Similarly, a drug intervention program targeting at-risk adolescents and including an 8-week structured exercise class reported a significant decrease in anxiety, depression, and substance use in those participants exhibiting an improvement in physical fitness (Collingwood et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a 12-week training program targeting adolescents and focusing on learning values and life skills through exercise reported a significant decrease in several risk factors associated with substance abuse and a concomitant reduction in the percentage of individuals who use cigarettes, smokeless tobacco, and alcohol (Collingwood et al, 2000). Similarly, a drug intervention program targeting at-risk adolescents and including an 8-week structured exercise class reported a significant decrease in anxiety, depression, and substance use in those participants exhibiting an improvement in physical fitness (Collingwood et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…2). Two articles in this review presented findings from more than one study that met inclusion criteria; one article described three studies (Pellegrini et al, 1995), and the other reported on six (Collingwood et al, 2000).…”
Section: Classification Of Studiesmentioning
confidence: 99%
“…Quender (2002) highlighted that children who took part in less physical activity had lower self-esteem and lower anxiety levels. Collingwood et al (2000) suggested that physical activity raised self-esteem. Trudeau and Shephard (2008) proposed that young people that take part in physical activity have reduced depression, anxiety symptoms and, they also observed a positive association between physical activity and academic improvements in performance.…”
Section: Physical Activity Interventions and Learning New Skillsmentioning
confidence: 99%
“…It is therefore recommended that primary schools use physical activity interventions especially for those children who are found to have low levels of self-esteem on school well-being measurements, but there would also be the potential for physical activity interventions to help support all children. Collingwood et al (2000) proposed physical activity can raise self-esteem, and following on from the positive results from this case study, the school has decided to continue with physical activity interventions, using a hole s hool app oa h to p o ote a g eate i ol e e t i ph si al a ti it (Rees et al 2001, p.6). These interventions will be particularly for children who are identified as having low self-esteem, especially to help support academic performance as well as a way of raising selfesteem.…”
Section: Recommendationsmentioning
confidence: 99%